A critical dislocation velocity for serration mechanism transition in a nickel-chromium solid solution alloy. (October 2021) - Qin, Yu; Greaney, P. Alex; Evans, T. Matthew; Kruzic, Jamie J.
Highlights: Serrated flow was investigated for a Ni-Cr alloy (Nimonic 75) under tension at 600 °C. Serrations change from Type A to Type C with decreasing strain rate and increasing strain. A critical dislocation velocity signifies the onset of Type C serration. The critical velocity is defined by the rate of solute rearrangement across dislocation cores. Abstract: The influence of strain rate across three orders of magnitude (1.70 × 10 −5 /s to 1.43 × 10 −2 /s) along with the effect of the plastic strain accumulation (up to 10%) on the serrated plastic flow were investigated in the nickel-chromium (Ni-Cr) solid solution alloy Nimonic 75 by performing constant-strain-rate tension testing at 600 °C. As the strain rate decreased, the critical strain for the onset of serrations transitioned from normal behavior to inverse behavior. The serrated flow was characterized as Type A+B serration at high strain rate (1.43 × 10 −2 /s). In the intermediate strain-rate regime (1.43 × 10 −3 /s and 1.45 × 10 −4 /s), Type B serrations were observed and followed by a transformation to Type C+B serrations. At the low strain rate (1.70 × 10 −5 /s), the plastic flow immediately displayed Type C serrations, which later evolved into Type C+B serrations. Regardless of the strain rate, plastic strain, or dislocation density, a critical dislocation velocity falling in the range of 1.2 × 10 −6 – 2.2 × 10 −6 m/s was identified to signify the onset of Type C serration, whereby the mobile dislocations break free from the solute cloud for short bursts of deformation. Finally, a novel model by solute rearrangement across dislocation cores was used to understand how the critical dislocation velocity is quantitatively determined by the rate at which solute atoms are able to hop across the glide plane as a partial dislocation core moves through the lattice. Graphical Abstract: Image, graphical abstract